2021
DOI: 10.1590/1413-81232021269.12122021
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade de adolescentes e adultos jovens brasileiros entre 1990 e 2019: uma análise do estudo Carga Global de Doença

Abstract: Resumo Trata-se de análise de indicadores de mortalidade de brasileiros com idades entre 10 e 24 anos. Foram analisados os dados do Global Burden of Disease (GBD) 2019, utilizando números absolutos, proporção de óbitos e taxas de mortalidade específicas entre 1990 e 2019, segundo faixa etária (10 a 14, 15 a 19 e 20 a 24 anos), sexo e causas de morte para Brasil, regiões e estados brasileiros. Houve redução de 11,8% nas taxas de mortalidade de indivíduos com idades entre 10 e 24 anos no período investigado. Em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
2
8
0
5
Order By: Relevance
“…The main findings of this study demonstrate that there is racial and gender inequality in the mortality of adolescents and young adults due to violence in Brazil. Corroborating the findings of this study, the results of the Global Burden of Disease 2019 revealed inequalities in the violent mortality of adolescents and young adults according to sex, causes, regions, and Brazilian-federated units 9,16 . Differentials in the risk of death of young people in the country are also explained by the household conditions and the living conditions in the municipalities and states; in Brazil, those poor young people living in more developed areas are more at risk of dying 16 .…”
Section: Discussionsupporting
confidence: 78%
“…The main findings of this study demonstrate that there is racial and gender inequality in the mortality of adolescents and young adults due to violence in Brazil. Corroborating the findings of this study, the results of the Global Burden of Disease 2019 revealed inequalities in the violent mortality of adolescents and young adults according to sex, causes, regions, and Brazilian-federated units 9,16 . Differentials in the risk of death of young people in the country are also explained by the household conditions and the living conditions in the municipalities and states; in Brazil, those poor young people living in more developed areas are more at risk of dying 16 .…”
Section: Discussionsupporting
confidence: 78%
“…Analysis of PNS data shows that 18.3% of people aged 18 and over said they experienced psy- chological, physical, or sexual violence in 2019. Within its scope, the PNS 2019 elucidates several issues and corroborates the findings of investigations of a strategic and operational nature in Brazil 4,[7][8][9][10][11][12] , although the final adjusted models were quite similar for all forms of violence, with the greatest differences being observed for sexual violence. We observed that urban life brings more risk (33%) than rural life, which is understandable because it is in the cities that people gather and where inequalities are concentrated 13,14 .…”
Section: Discussionsupporting
confidence: 68%
“…Malta et al 7 led a survey in Brazil with the same methodology used by Haagsma et al 19 and found, against all common sense, that here, too, deaths from violence, which were responsible for 134,931 deaths in 1990, dropped to 81,200, 22.8% less in 2015, with the main groups of causes being deaths and injuries due to homicides and transport accidents. Malta et al 9 repeated the study with data from 1990 to 2019 on deaths of adolescents and young people and showed a reduction of 30.8% in deaths of girls and 6.2% of boys. Corroborating the 2019 PNAD data, there was an increase in mortality rates in the North and Northeast regions, and a significant reduction in the Southeast and South regions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A análise dos dados da PNS mostra que 18,3% das pessoas com 18 anos ou mais disseram sofrer violência psicológica, física ou sexual em 2019. Dentro de seu escopo, a PNS 2019 elucida várias questões e corrobora com achados de investigações de cunho estratégico e operacional no Brasil 4,[7][8][9][10][11][12] , embora os modelos finais ajustados tenham sido bastante semelhantes para todas as formas de violência, sendo as maiores diferenças verificadas para a violência sexual. Observa-se que a vida urbana traz mais risco (33%) do que a rural, o que é compreensível porque é nas cidades que se aglomeram as pessoas e é onde se concentram as desigualdades 13,14 sobejamente atestado na literatura nacional e internacional [15][16][17][18] .…”
Section: Discussionunclassified